E-Panchayat in Kashmir: The Smart way forward - Sowkat Ahmad Dar; Dr. Naseer Ahmad Lone (Research Parks Publishers, 2022)
Jammu and Kashmir's government is promoting e-governance “Using information and communication technology (ICT) to bring simple, moral, accountable, responsive, and transparent (SMART) governance to the doorsteps of regular people at a reasonable cost.